GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 20 Sep 2018, 17:17

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If x + 1 = t and t = 3 – x, then x =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Manager
Manager
User avatar
S
Joined: 24 Oct 2016
Posts: 153
GMAT 1: 670 Q46 V36
If x + 1 = t and t = 3 – x, then x =  [#permalink]

Show Tags

New post 25 Aug 2018, 09:53
00:00
A
B
C
D
E

Difficulty:

  15% (low)

Question Stats:

88% (00:19) correct 12% (01:51) wrong based on 17 sessions

HideShow timer Statistics

If x + 1 = t and t = 3 – x, then x =

A) -2
B) -1
C) 0
D) 1
E) 2

_________________

Verb Tenses Simplified

If you found my post useful KUDOS are much appreciated.

Director
Director
User avatar
G
Joined: 20 Feb 2015
Posts: 733
Concentration: Strategy, General Management
Premium Member CAT Tests
Re: If x + 1 = t and t = 3 – x, then x =  [#permalink]

Show Tags

New post 25 Aug 2018, 10:34
dabaobao wrote:
If x + 1 = t and t = 3 – x, then x =

A) -2
B) -1
C) 0
D) 1
E) 2


I think we just have to substitute the respective values

x+1 = 3-x
2x=2
x=1
Board of Directors
User avatar
P
Status: QA & VA Forum Moderator
Joined: 11 Jun 2011
Posts: 4031
Location: India
GPA: 3.5
WE: Business Development (Commercial Banking)
GMAT ToolKit User Premium Member
If x + 1 = t and t = 3 – x, then x =  [#permalink]

Show Tags

New post 25 Aug 2018, 11:04
dabaobao wrote:
If x + 1 = t and t = 3 – x, then x =

A) -2
B) -1
C) 0
D) 1
E) 2

\(x + 1 = t\) and \(t = 3 – x\)

Substitute the value of "t"

\(x + 1 = 3 - x\)

Or, \(2x = 2\)

Or, \(x = 1\) , Answer must be (D)
_________________

Thanks and Regards

Abhishek....

PLEASE FOLLOW THE RULES FOR POSTING IN QA AND VA FORUM AND USE SEARCH FUNCTION BEFORE POSTING NEW QUESTIONS

How to use Search Function in GMAT Club | Rules for Posting in QA forum | Writing Mathematical Formulas |Rules for Posting in VA forum | Request Expert's Reply ( VA Forum Only )

If x + 1 = t and t = 3 – x, then x = &nbs [#permalink] 25 Aug 2018, 11:04
Display posts from previous: Sort by

If x + 1 = t and t = 3 – x, then x =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  

Events & Promotions

PREV
NEXT


GMAT Club MBA Forum Home| About| Terms and Conditions and Privacy Policy| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.